Ultrastructural localization of a platelet-derived growth factor/v-sis-related protein(s) in cytoplasm and nucleus of simian sarcoma virus-transformed cells. - Yeh, H J (1987)
The subcellular distribution of v-sis-related protein(s) was analyzed in three simian sarcoma virus (SSV)-transformed cell lines with immunofluorescence and protein A-gold labeling techniques using rabbit polyclonal anti-platelet-derived-growth factor (PDGF) antisera. Antigenically reactive proteins were recognized in subcellular organelles related to protein synthesis and processing, including polyribosomes, endoplasmic reticulum, and the Golgi apparatus, as well as on the cytoplasmic surface of plasma membranes. Prominent immunoreactive proteins were also shown in association with nuclear chromatin in intact cells and in isolated nuclei using Lowicryl K4M resin embedding techniques. Protein A-gold labeling was markedly reduced in sections of non-SSV-transformed fibroblasts incubated with anti-PDGF and absent from SSV-transformed cells if Epon resin was substituted for Lowicryl in the embedding process or if sections were with irrelevant antisera. Nuclear localization of v-sis-related antigens was confirmed in a nitrocellulose-based immunoassay using nuclei isolated from SSV-transformed fibroblasts. Thus, polypeptides recognized antigenically as related to the v-sis gene product not only may be found in subcellular organelles associated with protein synthesis and packaging but also may be found in the nucleus of SSV-transformed cells. These results raise the possibility that v-sis- or PDGF-like proteins may function within the nucleus of SSV-transformed cells.